2005
DOI: 10.1097/00054725-200502000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surgical Tissue From Patients with Crohnʼs Disease for the Presence of Mycobacterium avium Subspecies paratuberculosis DNA by In Situ Hybridization and Nested Polymerase Chain Reaction

Abstract: Crohn's disease (CD) is a chronic inflammatory bowel disease (IBD) with tissue granuloma and histopathological alteration that resembles aspects in tuberculosis, leprosy, and paratuberculosis. Mycobacterium avium subsp paratuberculosis (MAP) is the causative agent of paratuberculosis, with a suspected role in the etiology of CD. We investigated the presence of MAP DNA in 31 surgical tissue samples from 20 subjects using fluorescence in situ hybridization (FISH) with the aid of confocal scanning laser microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
1
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 34 publications
4
30
1
4
Order By: Relevance
“…paratuberculosis tests in the gut and the distribution of the gross inflammation in the Crohn's disease patients. This is in close agreement with the results of previous work (55). Mycobacterium avium subsp.…”
Section: Discussionsupporting
confidence: 94%
“…paratuberculosis tests in the gut and the distribution of the gross inflammation in the Crohn's disease patients. This is in close agreement with the results of previous work (55). Mycobacterium avium subsp.…”
Section: Discussionsupporting
confidence: 94%
“…paratuberculosis is transmitted from time to time to human populations in retail milk supplies (3,24,28,49). Recent research from several centers using appropriate laboratory methods showed that most people with chronic inflammation of the intestine of the Crohn's disease type are infected with this chronic enteric pathogen (2,9,53,63,66,67). Like that of Johne's disease, the incidence of Crohn's disease is increasing (43), particularly in children, with recent data from three sites in Northern and Central Europe and in Australia showing increases in the disease in children under 16 which average fivefold per decade (34,56,59).…”
mentioning
confidence: 99%
“…It can be based on culture or on culture-independent methods using specific probes. Despite intensive research focusing on Mycobacteria, Listeria, and Chlamydia, an infectious origin of IBD has not been confirmed (2,13,20,22,30). The global description strategy uses probes for large groups of bacteria which constitute the "dominant microbiota."…”
mentioning
confidence: 99%